Aerodynamic performance improvement and noise control for the multi-blade centrifugal fan by using bio-inspired blades. (15th January 2023) - Wang, Jiahao; Liu, Xiaomin; Tian, Chenye; Xi, Guang
Abstract: Inspired by the swimming characteristics of carps in the C-shaped starting posture, the bionic design of the blade is developed to improve the aerodynamic performance, reduce noise and conserve energy of multi-blade centrifugal fans. By adopting the reverse engineering method, the bionic equal-thickness blades (BETBs) inspired by the C-shaped starting mid-arc of carp are designed and optimized. Based on the comparison between numerical and experimental results of the aerodynamic performance of fan, the optimal bionic equal-thickness blade (O-BETB) is obtained. When the O-BETEs are applied to the original fan, the flow rate is increased by 6.8% and the noise is reduced by 0.5 dB(A). Further, the reconstructed geometric profile of fish body is coupled into the O-BETB to improve the aerodynamic performance of the fan. The results show that the flow rate with the coupled bionic blades (CBB) is increased by 8.3%, while the noise is reduced by 1.1 dB(A), and the power and efficiency are also optimized. The internal flow field, sound field and acoustic characteristics are analyzed to reveal the generation mechanism of aerodynamic noise. The aerodynamic noise of the fan is mainly concentrated in the low and middle frequency range, and its propagation process has obvious dipole characteristics. Meanwhile, because the profile of CBB is more in line with the flow characteristics in the fan, the separation vortex and secondary-flow vortex in the impeller channel and the unsteady interaction between the blade wake-flow and the volute are significantly suppressed, which is also the main reason for the CBB to reduce the noise. Highlights: Centerline and cross-section of carps in C-shaped starting posture are extracted. Bionic blade design methods of multi-blade centrifugal fan are proposed. Internal flow field and sound field characteristics are analyzed. Bionic features of blades improve the aerodynamic performance and reduce the noise.